1996
DOI: 10.1080/09595239600186101
|View full text |Cite
|
Sign up to set email alerts
|

Dope busts in the West: minor cannabis offences in the Western Australian criminal justice system

Abstract: Proponents of cannabis law reform argue that many people who are convicted for minor cannabis offences have no prior criminal conviction and are otherwise law-abiding citizens. This study of criminal justice system data in a strict prohibition jurisdiction (Western Australia) found that over 10% of all charges and 85% of all drug charges were for cannabis. Approximately 90% of these were for minor offences. Over 40% of those charged with cannabis possession/use as their most serious offence had never been arre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

1999
1999
2016
2016

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 3 publications
0
12
0
Order By: Relevance
“…Most are arrested for possession of small amounts of cannabis and rarely have a past criminal record (Lenton, 1999). Within this group there is little evidence that any criminal sanction -arrest or convictionreduces cannabis use (Lenton et al, 2000;Fergusson et al, 2003) or contributes to longer-term desirable social outcomes (Lenton et al, 2000).…”
Section: Introductionmentioning
confidence: 99%
“…Most are arrested for possession of small amounts of cannabis and rarely have a past criminal record (Lenton, 1999). Within this group there is little evidence that any criminal sanction -arrest or convictionreduces cannabis use (Lenton et al, 2000;Fergusson et al, 2003) or contributes to longer-term desirable social outcomes (Lenton et al, 2000).…”
Section: Introductionmentioning
confidence: 99%
“…Research suggests that a large number of people who are convicted for minor drug offences have no prior criminal record and are basically lawabiding citizens. Rather, they have a drug problem that contributes to their involvement in criminal acts (Ali et al, 1998;Lenton, Ferrante, & Loh, 1996): that is, they become engaged in criminal activity to finance their drug habit or as a consequence of intoxication (Kevin, 1997;Makkai, 1999;Rigg & Indermauer, 1996). However, there is also evidence that crime (including delinquency) predicts substance abuse cross-sectionally (Moss & Kirisic, 1995) and longitudinally (Stice, Myers, & Brown, 1998a, 1998b, and that delinquency often precedes the onset of substance use (Baumrind, 1991;Kandel & Davies, 1992).…”
mentioning
confidence: 99%
“…However, its major health risks are likely to be among long-term, regular users [12]. Research indicates that most people who receive a criminal conviction for a minor cannabis offence are otherwise law-abiding [13]. A cannabis conviction can have significant adverse impacts on employment, further involvement with the criminal justice system, relationships and accommodation; however, conviction fails to deter future cannabis use by many of those apprehended [14,15].…”
Section: Necessary Conditions For a Successful Schemementioning
confidence: 99%
“…Similarly, the introduction of the Cannabis Cautioning and Mandatory Education System in WA, where research had showed more than eight in 10 people facing court on cannabis possession received a criminal conviction [13], could be construed in part as an attempt to take the wind out of calls to introduce cannabis law reform. In March 2000 the Liberal Government introduced the Cannabis Cautioning and Mandatory Education System across the state, after a 12-month trial in two police districts.…”
Section: Some Policy Windows Close and Others Openmentioning
confidence: 99%